Implementing a structured model for osteoarthritis care in primary healthcare: A stepped-wedge cluster-randomised trial. - Nina Østerås; Tuva Moseng; Leti van Bodegom-Vos; Krysia Dziedzic; Ibrahim Mdala; Bård Natvig; Jan Harald Røtterud; Unni-Berit Schjervheim; Thea Vliet Vlieland; Øyvor Andreassen; Jorun Nystuen Hansen; Kåre Birger Hagen (PLoS Medicine)
Background To improve quality of care for patients with hip and knee osteoarthritis (OA), a structured model for integrated OA care was developed based on international recommendations. The objective of this study was to assess the effectiveness of this model in primary care. Methods and findings We conducted a cluster-randomised controlled trial with stepped-wedge cohort design in 6 Norwegian municipalities (clusters) between January 2015 and October 2017. The randomised order was concealed to the clusters until the time of crossover from the control to the intervention phase. The intervention was implementation of the SAMBA model, facilitated by interactive workshops for general practitioners and physiotherapists with an update on OA treatment recommendations. Patients in the intervention group attended a physiotherapist-led OA education and individually tailored exercise programme for 8-12 weeks. The primary outcome was patient-reported quality of care (OsteoArthritis Quality Indicator questionnaire; 0-100, 100 = optimal quality) at 6 months. Secondary outcomes included patient-reported referrals to physiotherapy, magnetic resonance imaging (MRI), and orthopaedic surgeon consultation; patients' satisfaction with care; physical activity level; and proportion of patients who were overweight or obese (body mass index ≥ 25 kg/m2). In all, 40 of 80 general practitioners (mean age [SD] 50 [12] years, 42% females) and 37 of 64 physiotherapists (mean age [SD] 42 [8] years, 65% females) participated. They identified 531 patients, of which 393 patients (mean age [SD] 64 [10] years, 71% females) with symptomatic hip or knee OA were included. Among these, 109 patients were recruited during the control periods (control group), and 284 patients were recruited during interventions periods (intervention group). The patients in the intervention group reported significantly higher quality of care (score of 60 versus 41, mean difference 18.9; 95% CI 12.7, 25.1; p < 0.001) and higher satisfaction with OA care (odds ratio [OR] 12.1; 95% CI 6.44, 22.72; p < 0.001) compared to patients in the control group. The increase in quality of care was close to, but below, the pre-specified minimal important change. In the intervention group, a higher proportion was referred to physiotherapy (OR 2.5; 95% CI 1.08, 5.73; p = 0.03), a higher proportion fulfilled physical activity recommendations (OR 9.3; 95% CI 2.87, 30.37; p < 0.001), and a lower proportion was referred to an orthopaedic surgeon (OR 0.3; 95% CI 0.08, 0.80; p = 0.02), as compared to the control group. There were no significant group differences regarding referral to MRI (OR 0.6; 95% CI 0.13, 2.38; p = 0.42) and proportion of patients who were overweight or obese (OR 1.3; 95% CI 0.70, 2.51; p = 0.34). Study limitations include the imbalance in patient group size, which may have been due to an increased attention to OA patients among the health professionals during the intervention phase, and a potential recruitment bias as the patient participants were identified by their health professionals. Conclusions In this study, a structured model in primary care resulted in higher quality of OA care as compared to usual care. Future studies should explore ways to implement the structured model for integrated OA care on a larger scale. Trial registration ClinicalTrials.gov NCT02333656.